2016
DOI: 10.2147/mnm.s52956
|View full text |Cite
|
Sign up to set email alerts
|

Matrix metalloproteinases as potential fecal biomarkers for ulcerative colitis – a function beyond their proteolytic activity

Abstract: Specific, sensitive, and noninvasive biomarkers are the most relevant tools to monitor activity, early stage detection, and the treatment management of ulcerative colitis (UC). Although, there is no single "Gold Standard" test for the diagnosis of UC, clinicians utilize a combination of clinical score, histological score, and colonoscopy index to assess disease activity and to predict the outcome of the disease. Over a decade, different biomarkers from body fluids have been considered to assess UC. The disadva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 80 publications
0
1
0
Order By: Relevance
“…It is possible that MMP-2 and/or MMP-9 may have potential utility as serum or plasma markers. 90 Many studies have indicated that there is a relationship between upregulation of MMP-1, MMP-2, MMP-7, MMP-9, and MMP-13 and poor survival and worse outcome, and it has been proposed that these MMPs could be used as prognostic, diagnostic, and therapeutic biomarkers in patients with CRC. [91][92][93] In a study, Jonsson et al assessed the expression levels of various MMPs, including MMP-1, MMP-2, MMP-8, MMP-9, and MMP-13, in different cancers.…”
Section: Circulating Levels Of Mmp As Different Body-fluid Biomarkersmentioning
confidence: 99%
“…It is possible that MMP-2 and/or MMP-9 may have potential utility as serum or plasma markers. 90 Many studies have indicated that there is a relationship between upregulation of MMP-1, MMP-2, MMP-7, MMP-9, and MMP-13 and poor survival and worse outcome, and it has been proposed that these MMPs could be used as prognostic, diagnostic, and therapeutic biomarkers in patients with CRC. [91][92][93] In a study, Jonsson et al assessed the expression levels of various MMPs, including MMP-1, MMP-2, MMP-8, MMP-9, and MMP-13, in different cancers.…”
Section: Circulating Levels Of Mmp As Different Body-fluid Biomarkersmentioning
confidence: 99%